Rhythm and melody as social signals for infants. Issue 1 (7th March 2018) - Cirelli, Laura K.; Trehub, Sandra E.; Trainor, Laurel J.
Abstract: Infants typically experience music through social interactions with others. One such experience involves caregivers singing to infants while holding and bouncing them rhythmically. These highly social interactions shape infant music perception and may also influence social cognition and behavior. Moving in time with others—interpersonal synchrony—can direct infants' social preferences and prosocial behavior. Infants also show social preferences and selective prosociality toward singers of familiar, socially learned melodies. Here, we discuss recent studies of the influence of musical engagement on infant social cognition and behavior, highlighting the importance of rhythmic movement and socially relevant melodies.